Review of research on environmental noise standards/policies/guidelines and measurement methodology in high-speed rail. (October 2022) - Srivastava, Sandeep; Sivasankar, Govindu; Dua, Gautam
Noise generated by rolling stock in High-Speed Rail (HSR) is of paramount importance from environment point of view. A lot of developments and improvements have happened in rolling stock design to reduce noise during running. There exists different standards and methodology for measurement of noise emanating from running of rolling stock at a high-speeds. This paper first discusses the basic concept of noise and then analyses various standards being followed mainly in Europe and Japan; compares them and draws inference in Indian context where the first HSR line, MAHSR (Mumbai Ahmedabad High Speed Rail) is under construction and several others are in planning stage.